Analysis of the Relationship between the Implementation of Circular Economy Principles and Financial Inclusion to Poverty Alleviation in Indonesia - Idrus, Rini Angriani; Sudarmanto, Eko; Muhtadi, Muhamad Ammar (West Science Social and Humanities Studies, 2024)
This qualitative study explores the relationship between circular economy principles, financial inclusion, and poverty alleviation in Indonesia. Through semi-structured interviews with key informants representing various stakeholders, the research investigates the integration of circular economy initiatives into financial inclusion strategies, the impact of circular economy practices on poverty alleviation, and the challenges and opportunities for sustainable development. The findings reveal potential synergies between circular economy and financial inclusion, highlighting the role of innovative financing mechanisms, capacity building, and policy reforms in promoting inclusive growth and environmental sustainability. However, significant barriers, including risk perception, collateral requirements, and regulatory constraints, pose challenges to accessing finance for circular businesses and entrepreneurs. Addressing these barriers requires collaborative efforts from policymakers, financial institutions, and other stakeholders to create an enabling environment for circular economy investments and foster inclusive development. The study underscores the importance of holistic and integrated approaches to sustainable development, where circular economy principles and financial inclusion strategies are mutually reinforcing, contributing to shared prosperity and well-being for all Indonesians.